129I record of nuclear activities in marine sediment core from Jiaozhou Bay in China. (April 2016) - Fan, Yukun; Hou, Xiaolin; Zhou, Weijian; Liu, Guangshan
Abstract: Iodine-129 has been used as a powerful tool for environmental tracing of human nuclear activities. In this work, a sediment core collected from Jiaozhou Bay, the east coast of China, in 2002 was analyzed for 129 I to investigate the influence of human nuclear activities in this region. Significantly enhanced 129 I level was observed in upper 70 cm of the sediment core, with peak values in the layer corresponding to 1957, 1964, 1974, 1986, and after 1990. The sources of 129 I and corresponding transport processes in this region are discussed, including nuclear weapons testing at the Pacific Proving Grounds, global fallout from a large numbers of nuclear weapon tests in 1963, the climax of Chinese nuclear weapons testing in the early 1970s, the Chernobyl accident in 1986, and long-distance dispersion of European reprocessing derived 129 I. The very well 129 I records of different human nuclear activities in the sediment core illustrate the potential application of 129 I in constraining ages and sedimentation rates of the recent sediment. The releases of 129 I from the European nuclear fuel reprocessing plants at La Hague (France) and Sellafield (UK) were found to dominate the inventory of 129 I in the Chinese sediments after 1990, not only the directly atmospheric releases of these reprocessing plants, but also re-emission of marine discharged 129 I of these reprocessing plants in the highly contaminated European seas. Graphical abstract: Highlights: Sediment core of Jiaozhou Bay well recorded the nuclear activities in the past 60 years. Signals of weapons testing at PPG and China were well documented in the sediment. Chernobyl accident signal was clearly recorded in the sediment core. European reprocessing releases dominates the present 129 I in North China. Reemission from European seawater is an important source of 129 I in North China.